3D rock thickness extraction by combining Point Clouds of different origin. Case Study: The roof of Koutouki Cave Peania, Greece - Konsolaki, A.; Vassilakis, Emm.; Giannopoulos, V.; Kontostavlos, G.; Psaltakis, I. (15th International Congress of the Geological Society of Greece, 2019)
The purpose of this research is to combine two state-of-the-art technologies in surveying for extracting the rock thickness above a cavity. By combining Lidar technology for indoor surveying and photogrammetric processing of Unmanned Aerial Systems (UAS – drones) data, we managed to calculate and project with high accuracy the rock thickness of the roof of the underground environment of Koutouki Cave (Peania, Greece). Usually, cave systems are complex and unique because of their distinctive geometry and compound geomorphology along with natural harsh conditions such as constrained accessibility, limited light, high humidity and possible existence of water. Such environments make mapping difficult and further complicated (Kershaw, 2012). Nowadays, the state-of-the-art in surveying of open surface is based on LiDAR technology. Lately, similar technology has started to be used for indoor surveying and consequently in cave mapping, especially where the underground space allows it. Our research was based on the use of a recently released piece of equipment introducing a lightweight mobile handheld laser scanning system (GeoSLAM ZEB – REVO) that has the ability to produce a quite dense point cloud within an underground cavity. The x, y, z point cloud is generated while the operator walks through the cave (Zlot and Bosse, 2014). The specifications of this equipment include a 360o rotation, a (class 1 eye safe) 100Hz laser – making 100 rotations per second with the collection of 43,200 points per second. The maximum effective range is around 25-30m for indoor environment and data over 30m are usually excluded.